Faktor-Faktor yang Mempengaruhi Produktivitas Tenaga Kerja di Kabupaten/Kota Provinsi Nusa Tenggara Timur - Brelia Zohana; Selli Nelonda (Universitas Negeri Padang, 2025)
The purpose of this study is to analyze and identify the extent to which the variables of education, health, wages, and labor force participation influence labor productivity in the regency/city areas of East Nusa Tenggara Province. This study uses panel data consisting of 22 regencies/cities over the period 2015-2023. The analysis method used in this study is panel data regression with the best model, namely the Fixed Effect Model (FEM). Based on the panel data regression test, the results show that partially, education has a negative and insignificant effect on labor productivity, whereas health, wages, and labor force participation have a positive and significant effect on labor productivity in East Nusa Tenggara Province. Simultaneously, the variables of education, health, wages, and labor force participation show a positive and significant influence on labor productivity in the regency/city areas of East Nusa Tenggara. Keywords: Labor Productivity, Education, Health, Wages, Labor Force Participation